The Greening Movement in Villages as an Investment for the Future Environment - Rizky Dwi Cantika; Farhan Ilham Apriyanto; Muhamad Kaka; Royke Tarius; Suci Rahayu; Siti Hanila; Maryaningsih Maryaningsih; Ami Pradana (Jurnal Pengabdian Mandiri, 2026)
Efforts for reforestation in the village are a crucial measure to safeguard the environment and enhance the well-being of the community. The Betungan Village RT 30 RW 05 is currently facing an environmental issue, specifically the insufficient number of trees, which leads to increased temperatures in the area, making it uncomfortable. This situation encourages the implementation of greening actions as a way to invest in the environment for the future. This article aims to explain the implementation and benefits of the greening initiative in Betungan Village, RT 30 RW 05, in supporting sustainable environmental development. The method used is a descriptive qualitative approach that involves observing in the field, documenting activities, and directly engaging the community in the tree planting process. The results of this activity indicate that greening efforts have positive effects on the environment, such as improved temperature comfort, increased green space, and heightened public awareness of the importance of preserving nature. In addition to benefiting the environment, this activity also enhances community involvement in supporting environmental programs in the village. The cultivation of green plants and crops that can produce is considered to have the potential for long-term benefits, both environmentally and economically. Therefore, the greening efforts in Betungan Village, RT 30 RW 05, serve not only as a response to the current environmental issues but also act as a sustainable investment for the quality of the environment and the well-being of future generations over the long term.